Idea Virtus na monetach cesarza Konstantyna Wielkiego. Typy VIRTVS MILITVM, VIRTVS EXERCITVS, VIRTVS EXERCITVS GALL, VIRTVS PERP AVG i VIRT CONSTANTINI AVG - Łuć, Ireneusz (Vox Patrum, 2023)
The first years of Constantine’s reign in Britain and Gaul were largely a continuation of the mode of government established by Emperor Diocletian. It was in this "old spirit" at the turn of the third and fourth centuries after the birth of Christ that the idea of Virtus, which was then placed on coins, was also represented. Through an analysis of the mint series, however, it is possible to grasp a foreshadowing of those downright revolutionary future changes that the recognition of Christianity as a fully legal religion within the Roman state would bring. The idea of Virtus itself will also undergo a significant transformation, including its adaptation to Christian doctrine. The intention of the author of this text, in relation to the title problem, is therefore to show the context of these extremely important and soon-to-be changes in the Roman state.